Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 72048 by ahmadshahhimat775@gmail.com last updated on 23/Oct/19

Answered by mind is power last updated on 23/Oct/19

a_2 =(6/(1+3))=(3/2)=((3.2^0 )/2)=((2+1)/2)=((2+2^0 )/2)  a_3 =(3/(1+(3/2)))=(6/5) =((3.2)/(3.2−1))=((4+2)/(4+2−1))=((2+2^2 )/(2+2^2 −1))  a_4 =(((12)/5)/((11)/5))=((12)/(11))=((3.2^2 )/(3.2^2 −1))=((2^3 +2^2 )/(2^3 +2^2 −1))  a_5 =((24)/(23))=((3.2^3 )/(3.2^3 −1))=((2^4 +2^3 )/(2^4 +2^3 −1))  a_n =((2^(n−1) +2^(n−2) )/(2^(n−1) +2^(n−2) +1)) if n≥2  a_1 =3  assum a_n =((2^(n−1) +2^(n−2) )/(2^(n−1) +2^(n−2) −1)),a_(n+1) =((2^(n+1−1) +2^(n+1−2) )/(2^(n+1−1) +2^(n+1−2) −1))?  a_(n+1) =((2.((2^(n−1) +2^(n−2) )/(2^(n−1) +2^(n−2) −1)))/(1+((2^(n−1) +2^(n−2) )/(2^(n−1) +2^(n−2) −1))))=((((2^(n+1−1) +2^(n+1−2)  )/(2^(n−1) +2^(n−2) −1))  )/((2^(n−1) +2^(n−1) +2^(n−2) +2^(n−2) −1)/(2^(n−1) +2^(n−2) −1)))  =((2^(n+1−1) +2^(n+1−2) )/(2^(n+1−1) +2^(n+1−2) −1))

a2=61+3=32=3.202=2+12=2+202a3=31+32=65=3.23.21=4+24+21=2+222+221a4=125115=1211=3.223.221=23+2223+221a5=2423=3.233.231=24+2324+231an=2n1+2n22n1+2n2+1ifn2a1=3assuman=2n1+2n22n1+2n21,an+1=2n+11+2n+122n+11+2n+121?an+1=2.2n1+2n22n1+2n211+2n1+2n22n1+2n21=2n+11+2n+122n1+2n212n1+2n1+2n2+2n212n1+2n21=2n+11+2n+122n+11+2n+121

Terms of Service

Privacy Policy

Contact: info@tinkutara.com